2021
DOI: 10.3390/ijms222111303
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity and Mechanism of Action of Hormonotoxin, an LHRH Analog Conjugated to Dermaseptin-B2, a Multifunctional Antimicrobial Peptide

Abstract: Prostate cancer is the most common cancer in men. For patients with advanced or metastatic prostate cancer, available treatments can slow down its progression but cannot cure it. The development of innovative drugs resulting from the exploration of biodiversity could open new therapeutic alternatives. Dermaseptin-B2, a natural multifunctional antimicrobial peptide isolated from Amazonian frog skin, has been reported to possess antitumor activity. To improve its pharmacological properties and to decrease its pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…These new formulations, Alg NPs + DRS-B2 or Alg NPs + DRS-B2 + menthol or lactic acid as a therapeutic, fulfill environmental constraints and meet societal expectations. Related to environmental constraints, alginate is considered as a biodegradable and biocompatible polymer, already used for cell encapsulation [ 29 , 30 , 31 ]. Previous studies have reported the application of Alg NPs as a vector to ascertain drug delivery [ 50 ], as well as a biosensor molecule [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These new formulations, Alg NPs + DRS-B2 or Alg NPs + DRS-B2 + menthol or lactic acid as a therapeutic, fulfill environmental constraints and meet societal expectations. Related to environmental constraints, alginate is considered as a biodegradable and biocompatible polymer, already used for cell encapsulation [ 29 , 30 , 31 ]. Previous studies have reported the application of Alg NPs as a vector to ascertain drug delivery [ 50 ], as well as a biosensor molecule [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hemolytic activities of Alg NPs (0.002 mg/mL to 2.000 mg/mL) or DRS-B2 (0.026 mg/mL to 0.208 mg/mL) or Alg NPs (0.500 mg/mL) with DRS-B2 (0.002 mg/mL to 0.208 mg/mL) were determined on fresh human erythrocytes obtained from a healthy donor, as previously described [ 30 ]. Cells treated with 0.2% Triton X100 were used as a positive control (CTL+) and correspond to the total (100%) of hemolytic activity.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a synthetic hormonotoxin molecule composed of dermaseptin-B2 associated with luteinizing hormone-releasing hormone (LHRH) was tested to improve the peptide’s antitumor activity, reducing its peripheral toxicity and lethality. This hormonotoxin displayed an anticancer effect very similar to DRS-B2 both in vitro and in vivo [ 86 ]. The LHRH addition to dermaseptin-B2 does not alter the peptide’s secondary structure and biological function [ 86 ].…”
Section: Dermaseptins and Anticancer Therapymentioning
confidence: 99%
“…This hormonotoxin displayed an anticancer effect very similar to DRS-B2 both in vitro and in vivo [ 86 ]. The LHRH addition to dermaseptin-B2 does not alter the peptide’s secondary structure and biological function [ 86 ]. On the other hand, double staining flow cytometry analysis showed that this hormonotoxin induced apoptosis instead of a necrotic process caused by DRS-B2 [ 86 ].…”
Section: Dermaseptins and Anticancer Therapymentioning
confidence: 99%
“…For patients with advanced and metastatic disease, the available treatment is limited to delaying the progression of the tumor. Couty et al [ 19 ] have examined a natural multifunctional antimicrobial peptide, dermaseptin-B2, that has shown some antitumor activity. To improve its pharmacological properties and decrease its peripheral toxicity and lethality, the authors have developed a hormonotoxin molecule composed of dermaseptin-B2 combined with d-Lys 6 -LHRH protein to target the luteinizing hormone-releasing hormone (LHRH) receptor.…”
mentioning
confidence: 99%